Simplification of feature-based 3D CAD assembly data of ship and offshore equipment using quantitative evaluation metrics. (February 2015) - Kwon, Soonjo; Kim, Byung Chul; Mun, Duhwan; Han, Soonhung
Abstract: In the design process for ship outfitting and offshore plants, an equipment catalog database is compiled in order for shipyards to reutilize data effectively. However, the current procedure for building such a catalog causes wastage of time because the modelers in the shipyard must perform manual modeling of the 3D CAD data in order to decrease the size of 3D CAD data and adopt a different level of detail (LOD) depending on the purpose of its use. This problem arises because equipment suppliers are not willing to give all of their 3D CAD data to shipyards, out of fear of the loss of intellectual property. Moreover, the 3D CAD data of equipment suppliers have a high LOD, while a shipyard's 3D CAD data have a relatively low LOD. Therefore, it is necessary to introduce an automated method to simplify the 3D CAD assembly data for equipment that is received from the equipment supplier. In addressing this problem, this study first proposes criteria for a simplification process and quantitative evaluation metrics for the simplification of 3D CAD assembly data, considering the characteristics of equipment data in the shipbuilding industry. Based on these findings, a simplification system was developed, and, four experimental test cases that were conducted on-site were used to verify the proposed system. The results showed that the data to be stored could be reduced to at least 25% of the original 3D CAD assembly data while ports, outer boundaries, and connectivity between CAD parts could be maintained. Graphical abstract: Highlights: Shipyards need simplified equipment 3D CAD assembly data for system-level design. Three simplification operations applicable for 3D CAD assembly data are developed. Evaluation metrics considering multiple simplification criteria are proposed. The evaluation metrics allow discriminatory priority of specific criteria.